The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland. Issue 6 (26th April 2018) - Moore, I.; Dodd, J. A.; Newton, M.; Bean, C. W.; Lindsay, I.; Jarosz, P.; Adams, C. E.
Abstract : A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.